RESEARCH ON PROCESSING METHODS OF PLANT WASTE FOR EXTRACTION OF CELLULOSIC FIBERS - BIO-BASED COATING FILLERS - HALYSH, VITA; VOROBYOVA, VICTORIA; MYRONYUK, OLEKSIY; TRUS, INNA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Lignocellulosic biomass, particularly agricultural residues, represents an abundant, renewable, and underutilized resource for the sustainable production of cellulose-based materials. It is mainly composed of cellulose, hemicelluloses, and lignin, which together form a complex, recalcitrant structure. These components can be selectively separated and transformed into value-added products through appropriate pre-treatment strategies. Among different agricultural by-products, corn stalks – an inevitable residue of large-scale maize cultivation – are of particular interest due to their high polysaccharide content, favorable fiber morphology, and constant availability. Their low economic value and lack of competition with food crops make them an attractive and sustainable feedstock. Valorizing corn stalks not only reduces agricultural waste but also supports circular economy principles, offering a renewable alternative to fossil-derived raw materials in the production of bio-based coatings, packaging, and composites. This study explores various methods of processing corn stalks to extract cellulosic fibers for potential use in bio-based coatings. The focus was on removing non-cellulosic components and their impact on the structure of the final product. Processing methods investigated include ethanol (ET), ethanol-benzene mixture (SB), hot water (HW), 1 % alkali solution (AT), deep eutectic solvents (DES) in various combinations, and peracetic acid. ET and SB provided the highest yields - 98.5 % and 96.4 % respectively, primarily removing extractive substances without significant structural changes. HW processing also yielded high at 91 %, removing only water-soluble components. Conversely, 1 % alkali solution reduced the yield to 83.5 % due to removal of low-molecular-weight hemicelluloses. The impact of DES was unexpected: it acted as an extractor rather than a delignifying agent (yielding 89.5 % for DES and 90.8 % for SB+DES). However, addition of hydrogen peroxide to DES significantly enhanced delignification by generating peracetic acid, resulting in product bleaching and enrichment with polysaccharides. The most profound delignifying effect was observed with peracetic acid treatment, producing a white, fine-fibrous product with minimal lignin content at 3 %. The findings provide valuable insights into tailoring pre-treatment strategies for lignocellulosic biomass, highlighting the potential of optimized processing routes for producing high-purity cellulose suitable for sustainable, bio-based coating applications.